Earle E. Jorgensen residence [interior] - George de Gennaro::::::photographer::: (1955)
Entrance to the Earle E. Jorgensen residence located at the Thunderbird Country Club in Riverside County, California. The project was completed in April, 1955 by architect William F. Cody and contractor Arthur J. Coffey.